The Influence of TNF-α, IL-6, TGF-β1, IFN-γ, IL-10 Polymorphisms on Predisposition to Diabetes Mellitus among Jordanian Patients - Khdair, Sawsan I.; Al-Naimat, Ola S.; Jarrar, Wassan; Al-Qerem, Walid; Khudeir, Feras A. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Diabetes mellitus is a long-term disorder with high prevalence globally. It can be classified into two types: Type 1 diabetes and Type 2 diabetes mellitus. Diabetes mellitus is considered a multifactorial disorder in which genetic factors such as cytokines play a major role. Cytokines play a role in immune modulation and are associated with the development of diabetes mellitus. Single nucleotide polymorphisms in cytokines were studied extensively in different populations to determine their association with a predisposition to diabetes mellitus. Objective: The aim of this study was to estimate the frequency of single nucleotide polymorphisms in the cytokine genes TNF-α, TGF-β, IL-6, IL-10, and IFN-γ in 102 Jordanian diabetes mellitus patients in comparison to 50 controls and their association to diabetes mellitus susceptibility. Methods: Analysis was performed using the highly specific polymerase chain reaction-sequence specific primers methodology. Results: Our findings showed that the IL-10-1082 G/G genotype (P = 0.02) and the TGF-β1 codon 25*G allele (P < 0.01) may be considered risk factors for type 2 diabetes mellitus. In addition, the IFN-γ-874*A allele (P = 0.04) seems to increase the predisposition to type 1 diabetes. Conclusion: Our study showed that the IL-10-1082 G/G genotype and TGF-β1 codon 25*G allele are associated with type 2 diabetes mellitus while the IFN- γ -874*A allele is associated with type 1 diabetes. Our findings may help in the early detection of diabetes mellitus, which would in turn help in undergoing the needed preventative measures to delay the onset of diabetes mellitus.
Keywords: polymorphisms